2022
DOI: 10.1002/jum.15987
|View full text |Cite
|
Sign up to set email alerts
|

Speckle‐Tracking Analysis in Fetuses With Tetralogy of Fallot: Evaluation of Right and Left Ventricular Contractility and Left Ventricular Function

Abstract: Objectives This study examines fetuses with tetralogy of Fallot (TOF) and evaluates the right (RV) and left (LV) ventricular contractility and LV function using speckle‐tracking analysis of the endocardium. Methods The study group consisted of 44 fetuses with TOF, of which 34% had pulmonary valve atresia (N = 15) and 59% (N = 26) had pulmonary valve stenosis. The RV and LV global fractional area change, longitudinal contractility (longitudinal strain, free wall strain, septal strain, free wall and septal annul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…This finding indicates the additive value of considering strain parameters of both, LV and RV, in the evaluation of fetal cardiac function. Using echocardiography, recent studies suggested that myocardial strain reflects the changing physiology in fetuses with CHD [ 23 25 ], e.g., altered strain parameters were observed in fetuses with tetralogy of Fallot [ 26 ]. In fetuses with transposition of the great arteries, echocardiographic strain measures predicted urgent postnatal intervention [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding indicates the additive value of considering strain parameters of both, LV and RV, in the evaluation of fetal cardiac function. Using echocardiography, recent studies suggested that myocardial strain reflects the changing physiology in fetuses with CHD [ 23 25 ], e.g., altered strain parameters were observed in fetuses with tetralogy of Fallot [ 26 ]. In fetuses with transposition of the great arteries, echocardiographic strain measures predicted urgent postnatal intervention [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…6 (2) The measurements can be obtained using the area and distance measurement tools available on all ultrasound machines and do not require speckle tracking analysis to perform as they have a high correlation for the LV area (0.96), RV area (0.98), LV length (0.97) RV length (0.97) LV midchamber width (0.95), and RV Base width (0.93) when compared to speckle tracking measurements. 10,24 (3) The measurements take less than 1 minute to perform once the end-diastolic image of the 4-chamber view is obtained. Supplement 3 is a video of the measurements from a fetus at 20 weeks and 1 day that took 48 seconds to complete the measurement sequence.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical benefits of measuring the 4CV and ventricles, as described in the current study, are the following: (1) The measurements would be compatible with the guidelines outlined for the Standard Ultrasound Examination endorsed by AIUM, ACOG, ARC, SMFM, and SRU 6 . (2) The measurements can be obtained using the area and distance measurement tools available on all ultrasound machines and do not require speckle tracking analysis to perform as they have a high correlation for the LV area (0.96), RV area (0.98), LV length (0.97) RV length (0.97) LV mid‐chamber width (0.95), and RV Base width (0.93) when compared to speckle tracking measurements 10,24 . (3) The measurements take less than 1 minute to perform once the end‐diastolic image of the 4‐chamber view is obtained.…”
Section: Discussionmentioning
confidence: 99%